2020
DOI: 10.3390/cancers12061596
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Pharmacokinetic Drug Resistance in Acute Myeloid Leukemia Cells with CDK4/6 Inhibitors

Abstract: Pharmacotherapy of acute myeloid leukemia (AML) remains challenging, and the disease has one of the lowest curability rates among hematological malignancies. The therapy outcomes are often compromised by the existence of a resistant AML phenotype associated with overexpression of ABCB1 and ABCG2 transporters. Because AML induction therapy frequently consists of anthracycline-like drugs, their efficiency may also be diminished by drug biotransformation via carbonyl reducing enzymes (CRE). In this study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Numerous studies have shown that the overexpression of the ABC transporters, ABCB1 and ABCG2, in certain types of solid tumors and leukemia, produce acquired drug resistance and attenuate, as well as abrogate, the efficacy of anticancer drugs with different chemical structures and mechanisms of action ( Mohammad et al, 2018 ; Boyer et al, 2019 ; Wu et al, 2020c ; Yang et al, 2021 ). It has been reported that palbociclib, a CDK4/6 inhibitor, may be a substrate of the ABCB1 and ABCG2 transporters ( De Gooijer et al, 2015 ; Parrish et al, 2015 ) and an ABCB1 chemosensitizer ( Fojo et al, 1985 ; Gao et al, 2017 ; Sorf et al, 2020 ). However, the exact interaction palbociclib with the ABCB1 and ABCG2 transporters remained to be determined, as this depends on the concentration range of the drug, the methodology and the activity of the transporters in the various cell types ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that the overexpression of the ABC transporters, ABCB1 and ABCG2, in certain types of solid tumors and leukemia, produce acquired drug resistance and attenuate, as well as abrogate, the efficacy of anticancer drugs with different chemical structures and mechanisms of action ( Mohammad et al, 2018 ; Boyer et al, 2019 ; Wu et al, 2020c ; Yang et al, 2021 ). It has been reported that palbociclib, a CDK4/6 inhibitor, may be a substrate of the ABCB1 and ABCG2 transporters ( De Gooijer et al, 2015 ; Parrish et al, 2015 ) and an ABCB1 chemosensitizer ( Fojo et al, 1985 ; Gao et al, 2017 ; Sorf et al, 2020 ). However, the exact interaction palbociclib with the ABCB1 and ABCG2 transporters remained to be determined, as this depends on the concentration range of the drug, the methodology and the activity of the transporters in the various cell types ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the penetration of palbociclib across the blood-brain barrier of ABCB1 and ABCG2 gene knockout mice was significantly decreased by ABCB1 and ABCG2 transporters, suggesting that palbociclib was a substrate for ABCB1 and ABCG2 transporters (De Gooijer et al, 2015). In contrast, studies by Gao et al (2017) and Sorf et al (2020) suggested that palbociclib may be an inhibitor of the ABCB1 transporter. Therefore, it is crucial to determine if palbociclib is a substrate or an inhibitor because if it is a substrate of the ABCB1 transporter, cancer cells that overexpress ABCB1 transporter will have lower intracellular levels of palbociclib, which could decrease or abrogate its efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the effect of DBF on cell cycle we used well-known CDK4/6 inhibitor palbociclib (PD-0332991) as a reference. Palbociclib was found to be a promising candidate to treat leukemia [ 19 , 50 , 51 ] and undergoes several clinical trials to treat different malignant disorders [ 22 , 52 ]. Earlier, brominated compounds were shown to affect cell growth, suggesting potential anti-cancer activity [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) remains a hematologic malignancy with extremely low cure and survival rates [ 1 ]. Only 29.5% of patients that are diagnosed with AML currently achieve 5-year survival, despite the overall progress in therapeutic strategies over the past decade [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%